2012
DOI: 10.5336/medsci.2011-27342
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality in Patients with Nosocomial Gram-Negative Bacteremia

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : Nosocomial bloodstream infections are serious health problems in hospitals all over the world. They are associated with a high rate of morbidity and mortality, prolonged hospital stay and higher costs. The aim of this study was to evaluate the clinical outcomes of the patients with gram-negative bacteremia and to identify the risk factors for mortality. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : A prospective observational study was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We identified 11 studies [20, 2224, 27, 29, 30, 35, 50, 54, 61], which included data on both T b and mortality in septic patients. From these, the patients could be divided in 12 subgroups, which served as the basis of the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 11 studies [20, 2224, 27, 29, 30, 35, 50, 54, 61], which included data on both T b and mortality in septic patients. From these, the patients could be divided in 12 subgroups, which served as the basis of the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of infections examined were bloodstream infections; only five studies evaluated patients with hospital-acquired pneumonia. Mortality was reported within 14 days (12 studies) and 30 days (22 studies) with two studies reporting at both time points [ 19 , 43 ]; the mortality time point was not documented in seven studies. Only four studies reported data on infection-related mortality [ 14 , 22 , 24 , 53 ].…”
Section: Resultsmentioning
confidence: 99%